Involving Engineering Student in Community-Based Project: A Qualitative Study - Amrulloh, Yusuf Aziz; fatuhrahmah, ufi; Murnani, Suatmi (Universitas Ahmad Dahlan, 2023)
Various studies on educational approaches explore the solution to fill the gap between education and society's demands. Specifically in the engineering field, addressing this gap is particularly urgent because previous research indicated that engineering graduates experienced this problem more frequently. On the other hand, our community needs them since engineering is the driver of innovation and community change. Community-based projects, combining community-based research and project-based learning approaches, are potential approaches to meet this purpose, although more research is needed. This study aims to explore students' experiences while involved in community-based projects, including the processes, experiences, feelings, and values obtained during the project. This study used a qualitative approach using an open-ended questionnaire and interviews with 39 engineering students. The results of the study show three main stages in a community-based project in the field of engineering and positive results in terms of cognitive, affective, skills, and values. The dynamics of the process and the potential for community-based project development are provided in the discussion and conclusion section.